Habitat and behavior of javan hawk-eagle (Nisaetus bartelsi) in SPTN 2 Majelengka Gunung Ciremai National Park, West Java - Adu, Steven Jonathan; Arief, Harnios; Sunarminto, Tutut (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
The existence of the Javan hawk-eagle depends on the condition of the forest in its habitat.  If the lowland forest is damaged, the Javan hawk-eagle will be pushed to the higher forest; This can affect the behavior of the Javan hawk-eagle because it is related to the availability of the game in each habitat type. This study aims to analyze the habitat conditions and behavior of the Javan hawk-eagle in Mount Ciremai National Park, using the checkered line method and focal animal sampling. Analysis of the Javan hawk-eagle habitat used a vegetation analysis approach and the level of use of habitat types. The results showed that the Javan hawk-eagle most often used natural forest habitat types (85.38%) at the Cipari site and plantation forests (83.14%) at the Bantar agung site. The dominant tree species in the natural forest are benda (Castanopsis argentea; 20.02%) and saninten (Artocarpus elasticus; 13.30%). Javan hawk-eagles choose trees to nest in kedondong trees (Spondias pinnata) and pine trees (Pinus merkusii ) in valleys between hills and close to water sources or rivers. Overall the behavior of the Javan hawk-eagle found is resting/perching, hunting, flying, and interacting. The most common behavior of Javan hawk-eagles found was resting/perching (80.16%) and interaction (45.88%).